Form and Function of Wemale Oral Literature in the Traditional Ceremony of King’s Inauguration in the Negeri Karlutu Warasiswa - Potimau, Evelin; Solissa, Everhard Markiano; Ratumalessy, Merlyn (Universitas Pattimura, 2023)
This study aims to describe the form and function of wemale oral literature in the traditional ceremony of inauguration of the king in the land of Karlutu Warasiwa, North West Seram District, Central Maluku Regency. The approach used in this study is a qualitative approach that prioritizes the research process and understanding based on a methodology that investigates a social phenomenon. The techniques used in data collection are observation techniques, recording techniques, interview techniques and recording techniques. There are three data analysis techniques, namely data reduction, data presentation, word interpretation and drawing conclusions. The results of the study show that there is oral literature used in the traditional inauguration of the king which is the language of the people and folk songs passed down from generation to generation in the traditional ceremony of the inauguration of the king which are conveyed using the regional language, namely Wemale language.